2012
DOI: 10.3390/ijms131012224
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Postoperative Hyperbaric Oxygen Treatment on Intra-Abdominal Adhesions in Rats

Abstract: Abdominal adhesions, whether caused by peritoneal trauma, radiation, infection, or a congenital condition, are associated with a wide range of complications. These complications include chronic abdominal or pelvic pain, infertility, and adhesive small bowel obstruction. Such adhesions render re-operation difficult, with attendant risks of inadvertent enterostomy and increased operation time. The purpose of this study was to investigate the potential of hyperbaric oxygen (HBO) therapy in the prevention of abdom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
11
0
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 22 publications
(21 reference statements)
1
11
0
1
Order By: Relevance
“…Accordingly, in the present study, both the collagen deposition and epidural adhesion decreased with the down-regulation of IL-6 and TGF-b1. Previous literatures and the present data may explain some if not all of the possible mechanisms that make HBO effective in preventing EF [15,26]. We hypothesize that the major mechanism of HBO on preventing EF was its beneficial role on reducing inflammatory cytokines [27].…”
Section: Discussionmentioning
confidence: 64%
“…Accordingly, in the present study, both the collagen deposition and epidural adhesion decreased with the down-regulation of IL-6 and TGF-b1. Previous literatures and the present data may explain some if not all of the possible mechanisms that make HBO effective in preventing EF [15,26]. We hypothesize that the major mechanism of HBO on preventing EF was its beneficial role on reducing inflammatory cytokines [27].…”
Section: Discussionmentioning
confidence: 64%
“…An experimental study showed that HBO ameliorates bacterial translocation in rats with mechanical intestinal obstruction. Chen and colleagues demonstrated the efficacy of HBO therapy in a rat peritoneal adhesion model. Abu‐Asi and co‐workers reported the value of HBO in treating recurrent acute bowel obstruction after previous pelvic radiotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, they are the leading cause of intestinal obstructions in developed world [9] and are responsible for 20% -40% of infertility [5,10]. In addition to their morbidity, they may also result in prolonged operating time, inadvertent organs injuries and high financial cost [8,11].…”
Section: Introductionmentioning
confidence: 99%
“…Adhesions can cause important morbidity including abdominal and pelvic pain, intestinal obstructions, and infertility [8]. In fact, they are the leading cause of intestinal obstructions in developed world [9] and are responsible for 20% -40% of infertility [5,10].…”
Section: Introductionmentioning
confidence: 99%